2017
DOI: 10.1063/1.4993648
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical electronic structure of the cadmium monohalide molecules CdX (X = F, Cl, Br, I)

Abstract: The potential energy and dipole moment curves for the lowest electronic states in the representation 2s+1 Λ (±) of CdX (X = F, Cl, Br, I) molecules are investigated via complete active space self-consistent field (CASSCF) and multi-reference configuration interaction MRCI (single and double excitation with Davidson correction). For the bound states of CdX diatomic molecules the bond distances R e , the vibrational harmonic frequencies ω e , the rotational constants B e , the electronic energies relative to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…For CdI, they used B3LYP functional and pseudopotential basis set, however, without specifying small/large core in the basis set. Later, Badreddine and Korek reported multi-reference configuration interaction calculations (MRCI) study on CdI with pseudopotential basis set utilizing large core (46 electrons) [22]. Recently, Li et al [23] reported calculations utilizing pseudopotential basis sets on the ground and excited states of CdI.…”
Section: Introductionmentioning
confidence: 99%
“…For CdI, they used B3LYP functional and pseudopotential basis set, however, without specifying small/large core in the basis set. Later, Badreddine and Korek reported multi-reference configuration interaction calculations (MRCI) study on CdI with pseudopotential basis set utilizing large core (46 electrons) [22]. Recently, Li et al [23] reported calculations utilizing pseudopotential basis sets on the ground and excited states of CdI.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of theoretical studies on the halides and chalcogenides of transition metals motivated us to investigate the transition-metal halides in previous works. In the present research, we examine the CdSe and CdTe molecules.…”
Section: Introductionmentioning
confidence: 99%